Analisis Kinerja Keuangan Lembaga Pelatihan Kerja Kartika Sebagai Upaya Pencapaian Tujuan Organisasi - Waruwu, Erlin Kristinawati; Octafian, Ray (Universitas Sains dan Teknologi Komputer, 2024)
The objective of this study is to assess the financial performance of job training institutions with regards to the attainment of organisational objectives. This study used a qualitative methodology to assess the efficacy of managing financial resources within institutions. It focuses on important financial indicators, including liquidity, solvency, profitability, and efficiency. The study collected and analysed historical financial data from multiple job training institutions to ascertain the correlation between financial performance and the institution's capacity to accomplish its strategic objectives. The research findings indicate that institutions exhibiting robust financial performance are more proficient in conducting training programmes that align with labour market demands, extending the scope of their services, and guaranteeing long-term operational viability.